An efficient multiwavelength light source based on ASE slicing - Harun, Sulaiman Wadi; Rahman, Faidz Abd; Dimyati, Kaharudin; Ahmad, Harith (John Wiley & Sons, 2013)
A multiwavelength light source based on a flat-gain erbium-doped fiber amplifier (EDFA) and loop miffor is experimentally demonstrated for single-pass and double-pass scheme. IsoGain™ erbium-doped fiber is used as a gain medium for the EDFA, which has a flat-gain or 13.5 dB for the input power of O dBm with gain flatness of less than 1 dB at wavelength region from 1530 nm to 1570 nm. The loop mirror is constructed using a 3 dB coupler and polarization maintaining fiber (PMF). The source generates up to 25 channels within 10 nm bandwidth of 1550 nm region with a channel spacing of 0.4 nm. The channel spacing can be varied by controlling the length of the PMF. The output power of double-pass scheme is obtained at about -41 dBm, which is more than 15 dB higher compared with single-pass scheme. However, the signal to noise ratio is only about 4 dB for the double-pass scheme compared with more than 60 dB for the sinele-pass scheme. A graph is presented. Gain spectrum of the flat-gain EDFA at various input signal power.